Taxonomy of Simulium guaporense Py-Daniel (Diptera: Simuliidae) from Brazil, with the first description of males and females - Hamada, Neusa; Hernandez, Luis M.; Luz, Sergio Luiz Bessa (Zootaxa, 2006)
We describe Simulium guaporense Py-Daniel adults and redescribe some morphological characters of its larvae and pupae based on specimens collected near the type locality in Rondônia State, Brazil. We report this species for the first time in Mato Grosso State. This species was placed originally in the S. siolii species group of the subgenus Psaroniocompsa; however, the thoracic pattern of the adults of S. guaporense is similar to that of species in the S. auristriatum species group. The immature stages were found on deciduous leaves and trailing vegetation in sandy-bottomed streams. Females were collected biting humans.